The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0043076
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Lies and fMRI—Gender Differences in Neural Basis of Deception

Abstract: Deception has always been a part of human communication as it helps to promote self-presentation. Although both men and women are equally prone to try to manage their appearance, their strategies, motivation and eagerness may be different. Here, we asked if lying could be influenced by gender on both the behavioral and neural levels. To test whether the hypothesized gender differences in brain activity related to deceptive responses were caused by differential socialization in men and women, we administered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 55 publications
8
29
1
Order By: Relevance
“…Our findings indicated that, the lying trials both in deceiving for obtaining rewards and deceiving for avoiding punishments conditions led to significantly larger increase in HbO in the PFC than truth-telling trials in the control condition, which was similar to previous brain imaging studies [12,20]. Numerous studies have revealed the important role of the PFC in deception [10][11][12][13], which mainly reflected various executive functions of the brain [12,19].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our findings indicated that, the lying trials both in deceiving for obtaining rewards and deceiving for avoiding punishments conditions led to significantly larger increase in HbO in the PFC than truth-telling trials in the control condition, which was similar to previous brain imaging studies [12,20]. Numerous studies have revealed the important role of the PFC in deception [10][11][12][13], which mainly reflected various executive functions of the brain [12,19].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we mainly focused on the inhibition function of the brain during deception [12,18], and thus we selected one channel in the right IFG and one channel in left MFG as two regions of interest (ROIs) respectively according to topographic images.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations